Automatic Encoding of a View-Centered Background Image in the Macaque Temporal Lobe - Chen, He; Naya, Yuji (Cerebral cortex (New York, N.Y. 1991), 2020)
Abstract Perceptual processing along the ventral visual pathway to the hippocampus (HPC) is hypothesized to be substantiated by signal transformation from retinotopic space to relational space, which represents interrelations among constituent visual elements. However, our visual perception necessarily reflects the first person’s perspective based on the retinotopic space. To investigate this two-facedness of visual perception, we compared neural activities in the temporal lobe (anterior inferotemporal cortex, perirhinal and parahippocampal cortices, and HPC) between when monkeys gazed on an object and when they fixated on the screen center with an object in their peripheral vision. We found that in addition to the spatially invariant object signal, the temporal lobe areas automatically represent a large-scale background image, which specify the subject’s viewing location. These results suggest that a combination of two distinct visual signals on relational space and retinotopic space may provide the first person’s perspective serving for perception and presumably subsequent episodic memory.